2008
DOI: 10.1007/s00253-008-1496-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, production, and applications of gellan: current state and perspectives

Abstract: Bacterial exopolysaccharides (EPS) are products of biotechnology that are of high interest due to their rheological properties. This is the case of sphingans, a group of structurally related EPS secreted by members of the genus Sphingomonas. Among these, gellan is a multifunctional gelling agent produced in high yields by the non-pathogenic strain Sphingomonas elodea ATCC 31461. In its native form, gellan is a linear anionic EPS based on a tetrasaccharide repeat unit composed of two molecules of D: -glucose, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(141 citation statements)
references
References 49 publications
1
135
0
5
Order By: Relevance
“…In addition to their use as scaffolds or bioreactors, reinforced hydrogels that can endure significant mechanical loads are expanding their potential application in drug delivery systems, actuators and artificial muscles, sensors and conductors, photoresponsive gels, cosmetics and food applications [31][32][33][34][35][36][37][38][39]. The two hydrogels employed in this work to fabricate the scaffolds, agarose [40][41][42] and gellan [43][44][45][46], besides their traditional uses, have recently gained a new appreciation in the biomaterials and drug delivery research fields.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their use as scaffolds or bioreactors, reinforced hydrogels that can endure significant mechanical loads are expanding their potential application in drug delivery systems, actuators and artificial muscles, sensors and conductors, photoresponsive gels, cosmetics and food applications [31][32][33][34][35][36][37][38][39]. The two hydrogels employed in this work to fabricate the scaffolds, agarose [40][41][42] and gellan [43][44][45][46], besides their traditional uses, have recently gained a new appreciation in the biomaterials and drug delivery research fields.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity, purity, and physical characteristics of extracted gellan depend on many factors including cell population, nutrient feedstock, temperature, pH, and extraction procedure 28 . A detailed review of gellan gum biosynthesis can be found in Fialho et al 29 .…”
Section: Gellan Gum Sourcementioning
confidence: 99%
“…GDP-D-mannose is the donor of D-mannose, a sugar residue found in many bacterial extracellular polysaccharides, as is the case of xanthan, cepacian, acetan, and some sphingans (Becker et al, 1998;Cescutti et al, 2000;Richau et al, 2000;Griffin et al, 1997;Fialho et al, 2008). The synthesis of GDP-D-mannose from F6P requires the enzyme activities phosphomannose isomerase (PMI; EC 5.3.1.8), phosphomannose mutase (PMM; EC 5.4.2.8) and GDP-D-mannose pyrophosphorylase (GMP; EC 2.7.7.13) (Fig.…”
Section: Gdp-d-mannosementioning
confidence: 99%
“…This mutant exhibited a reduced ability to colonize a mouse model of infection and was not able to interact with the human gastric mucosa of biopsy specimens in situ. Some sugar polymers have applications in the food and pharmaceutical industries, like alginate, xanthan, gelan and polysaccharides from lactic acid bacteria (LAB) (Sabra et al, 2001;Becker et al, 1998;Fialho et al, 2008;Boels et al, 2001). These applications led to an increased interest in the study of the metabolic pathways leading to the formation of these polymers and their regulation, with the objective to optimize the microbial production process.…”
Section: Biotechnological Potential Of Nucleotide Sugar Metabolic Patmentioning
confidence: 99%